Control of elastic wave propagation in piezoceramic cylinders of sector cross section - Puzyrev, Vladimir; Valeriy, S. (2011)
In the present paper the problem of elastic waves propagation in piezo-ceramic cylindrical waveguides of noncircular cross section is studied for the cylinders of circular and hollow cross section with sector cut of arbitrary angular measure. Boundary surfaces of sector cut are covered by non-extensible membranes and cylindrical surfaces can have arbitrary boundary conditions. The equations of motion of the piezoelectric cylinder are analytically integrated and dispersion equations that exactly satisfy the boundary conditions are obtained. A selected set of numerical results including dispersion spectrums, distributions of cutoff frequencies and phase velocities for cylinders with various cross section geometry and boundary conditions is presented, and main effects of their transformation are discussed. Results are in good agreement with the results obtained by other researches for the special case of circular and hollow cylinders. The model can be used to control the dispersion spectrums and wave characteristics by changing the geometry and mechanical properties of the waveguides. © Springer Science + Business Media B.V. 2011.